Analisis Pelaksanaan Pembelajaran IPA Kelas V SD N 1 Bebalang - Ni Kadek Sinta Ulandari; Ni Wayan Sri Darmayanti; I Ketut Dedi Agung Susanto Putra (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to find out how grade 5 students implement science learning at SD N 1 Bebalang. The subjects in this research were 18 people who were class V students. The instruments used were interviews, observation sheets and documentation. The question to be answered in this research is: How is science learning implemented in class 5 of SD N 1 Bebalang?